Lignan (+)-Piperitol-γ,γ-Dimethylallylether from Stem Bark of Zanthoxylum rhetsa (Roxb.) DC (Rutaceae) - Ruchiyat Ruchiyat; Al Arofatus Naini; Tati Herlina; Iqbal Musthapa; Unang Supratman (Syarif Hidayatullah State Islamic University, 2022)
Lignans are a group of phenylpropanoid dimers in which the phenylpropane units are linked by their propyl side chains' central carbon (C8). Lignans have various biological activities, including antiviral, anticancer, cancer preventive, and cytotoxic. Zanthoxylum rhetsa (Roxb.) DC is a tree with prickly branchlets belonging to the Zanthoxylum genus, commonly known as panggal buaya in Indonesia. Asian tribes have used this plant as traditional medicine. In this study, (+)-piperitol-γ,γ-dimethylallylether, a furofuran lignan, was successfully isolated. The chemical structure of compound 1 was determined based on spectroscopic data, including 1D- and 2D-NMR, mass spectroscopy, and by comparing with previous spectral data. In addition, compound 1 was tested for its cytotoxic activity against MCF-7 breast cancer cell lines in vitro and showed weak activity with the IC50 value of 261.37 µg/mL.